A mentored hands-on training model for scaling up implementation and intervention research in India: "connecting the dots" - R Ransing, M Hawk (Health research policy and systems, 2023)
Despite the high burden of mental disorders in low- and middle-income countries (LMICs), less than 25% of those in need have access to appropriate services. The Grantathon is a successful model for building research capacity and improving mental health research in India that could be adopted for use in other LMICs.
Keywords: Grantathon, Mental health, Research mentoring